薬物供給管理用の管理システム (2017)
てんかんの治療または予防において薬物の供給を管理するシステムが提供される。前記システムの中央管理装置は、データ記憶装置と、該データ記憶装置に対してデータを読み書きするための一つまたは複数のプロセッサとを有する。前記データ記憶装置は患者記録のデータベースを含み、各患者記録は薬物認可フィールドを有する。前記中央管理装置は、患者の遺伝子検査結果に依存して該患者への抗てんかん薬の初回処方の認可を出力することができ、抗てんかん薬の後続の処方の認可の前に該患者のための後続の検査をスケジューリングする。また、当該システムが用途を見いだす方法が提供される。前記システムおよび方法は、てんかんの重症亜型または難治性てんかん（例えばドラベ症候群）の治療に用途を見いだす。 A system of controlling distribution of a medication in the treatment or prevention of epilepsy is provided. A central controller of the system has a data store and one or more processors for reading and writing data to the data store. The data store comprises a database of patient records, each patient record having a medication authorization field. The central controller can output an authorization of a first prescription of epilepsy medication to a patient in dependence upon genetic test results for the patient and schedules a subsequent test for the patient prior to authorization of a subsequent prescription of epilepsy medication. Also provided are methods in which the subject systems find use. The systems and methods find use in the treatment of severe subtypes of epilepsy or refractory epilepsy, such as Dravet Syndrome.